Sucrose preference test: A systematic review of protocols for the assessment of anhedonia in rodents - Primo, Maria João; Fonseca-Rodrigues, Diana; Almeida, Armando; Teixeira, Pedro M.; Pinto-Ribeiro, Filipa (European neuropsychopharmacology, 2023)
Anhedonia is described as a decreased ability to experience rewarding and enjoyable activities, a core symptom of major depressive disorder. The sucrose preference test (SPT) is a widely used and reliable behavioural test to assess anhedonia in rodents, based on a two-bottle choice paradigm. To date, different protocols are in use, inducing variability between researchers and hampering comparisons between studies. We performed a systematic review of the SPT protocols used in 2021 to identify the parameters in which they differ and their potential impact. We searched a total of four databases (PubMed, Scopus, Web of Science and Science Direct), from 1st January 2021 to 31st December 2021, and screened a total of 1066 articles. After screening by title and abstract, a total of 415 articles were included in this review. We extracted and analysed the different procedures used, the type of sweet solution and the habituation, deprivation, and testing protocols. The overall quality of the studies was considered very good, however, SPT protocols were extremely variable between studies with a total of 65 different habituation protocols and 104 combinations of food/water deprivation and preference testing duration. As the SPT is one of the most used tests to assess anhedonia in rodents, this work raises awareness of the great variability in SPT protocols being currently used. Furthermore, we call for standardization in the protocol used, and overall improvement of data reporting of methodologies and results, to increase the consistency between studies and allow a better comparison of results between different labs.